2010
DOI: 10.1007/s00221-010-2322-3
|View full text |Cite
|
Sign up to set email alerts
|

Gesture imitation in musicians and non-musicians

Abstract: Imitation plays a crucial role in the learning of many complex motor skills. Recent behavioral and neuroimaging evidence suggests that the ability to imitate is influenced by past experience, such as musical training. To investigate the impact of musical training on motor imitation, musicians and non-musicians were tested on their ability to imitate videoclips of simple and complex two-handed gestures taken from American Sign Language. Participants viewed a set of 30 gestures, one at a time, and imitated them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Taken together, musically trained participants outperform musically untrained participants in terms of accuracy in a real-time drawing task of pitch and loudness, which adds to the increasing literature of findings suggesting that musically trained participants' (sensori-)motor skills are transferable to other, non-specific domains (Spilka, et al, 2010). However, our results are limited insofar as they cannot disentangle musically trained participants' motoric skills from training effects of audio-visual mappings or basic auditory discrimination skills (but note that we attempted to minimize potential differences in the latter by choosing very simple sound stimuli and presenting them twice).…”
Section: Performance Accuracymentioning
confidence: 59%
“…Taken together, musically trained participants outperform musically untrained participants in terms of accuracy in a real-time drawing task of pitch and loudness, which adds to the increasing literature of findings suggesting that musically trained participants' (sensori-)motor skills are transferable to other, non-specific domains (Spilka, et al, 2010). However, our results are limited insofar as they cannot disentangle musically trained participants' motoric skills from training effects of audio-visual mappings or basic auditory discrimination skills (but note that we attempted to minimize potential differences in the latter by choosing very simple sound stimuli and presenting them twice).…”
Section: Performance Accuracymentioning
confidence: 59%
“…The parsing of streams of information, whether visual, as in sign language, or aural as in music or speech, involves the Brodmann 47 region of the brain (Levitin & Menon, 2003) and a recent study with deaf signers, deaf non-signers and hearing non-signers has shown that regions of the superior temporal cortex that normally respond to auditory linguistic stimuli not only adapt to perceive visual input (sign language) but also retain their original cognitive functionality (Cardin, Orfanidou, Ronnberg, Capek, Rudner, & Woll, 2013). People with musical training are better at copying gestures (Spilka, Steele, & Penhune, 2010) and autistic children's memory for hand signs accompanied by music is better than those accompanied by rhythms or speech (Buday, 1995). Conductors can also accurately recognise the emotional content of other conductors' gestures (Wöllner, 2012).…”
Section: Towards a Sign Language For Musicmentioning
confidence: 99%
“…Studies also found that musicians have performed better than non-musicians on auditory processing (Chartrand & Belin, 2006;Špajdel, Jariabková, & Riečanský, 2007;Strait, Kraus, Parbery-Clark, & Ashley, 2010) and fine motor abilities (Amunts et al, 1997;Hughes & Franz, 2007;Spilka, Steele, & Penhune, 2010).…”
Section: Introductionmentioning
confidence: 97%